2018
DOI: 10.1101/485763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial chromosome folding and active transcription drive DNA fragility and formation of oncogenic MLL translocations

Abstract: How spatial chromosome organization influences genome integrity is still poorly understood.Here we show that DNA double-strand breaks (DSBs) mediated by topoisomerase 2 (TOP2) activities, are enriched at chromatin loop anchors with high transcriptional activity. Recurrent DSBs occur at CTCF/cohesin bound sites at the bases of chromatin loops and their frequency positively correlates with transcriptional output and directionality. The physiological relevance of this preferential positioning is indicated by the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 81 publications
(118 reference statements)
1
18
0
Order By: Relevance
“…Recent works support a key function of genome architecture, TADs borders and loop extrusion in genome stability, including immunoglobulin loci rearrangements 36,37 and in DSB occurrence through topoisomerase reactions 38,39 . Our study shows that genome architecture is also instrumental for the correct establishment of H2AX and DDR foci formation, expanding the function of genome organization within TADs to the response to DNA damage.…”
mentioning
confidence: 91%
“…Recent works support a key function of genome architecture, TADs borders and loop extrusion in genome stability, including immunoglobulin loci rearrangements 36,37 and in DSB occurrence through topoisomerase reactions 38,39 . Our study shows that genome architecture is also instrumental for the correct establishment of H2AX and DDR foci formation, expanding the function of genome organization within TADs to the response to DNA damage.…”
mentioning
confidence: 91%
“…More recently, signal-induced DSBs, occur-ring upon transcription of early-response genes (following neuronal activation [Madabhushi et al, 2015], estrogen treatment [Ju et al, 2006], androgen induction [Haffner et al, 2010], serum induction [Bunch et al, 2015], and heat shock [Bunch et al, 2015]), have been revealed, adding to the complexity of mapping DSBs. Physiological DSBs are required for releasing the torsional tension that develops during transcription and replication, and at loop anchors involved in three-dimensional (3D) genome folding (Barlow et al, 2013;Canela et al, 2017Canela et al, , 2019Gothe et al, 2019;Ju et al, 2006;Madabhushi et al, 2015;Wei et al, 2016). In particular, DSBs and subsequent DDR signaling were shown to promote effective RNA polymerase II (Pol II) pause release and transcriptional elongation for induction of early-response genes (Bunch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2017) were able to assess the genome-wide off-target activity of two CRISPR-associated RNA-guided endonucleases, Cas9 and Cpf1, demonstrating that Cpf1 has higher specificity than Cas9. More recently, BLISS was used to map DSBs at sites involved in recurrent genome rearrangements and chromosomal translocations in cancer cells (Dellino et al, 2019;Gothe et al, 2019). Nevertheless, the landscape of DSBs across the genome and their repair in cancer cells is poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, they may utilize the association between CTCF and double strand breaks (52) to facilitate integration into the host genome. Regardless of the mechanism, these elements appear to exist in a symbiotic relationship with their hosts, harnessing host transcriptional machinery to proliferate while contributing substrates for regulatory innovation.…”
Section: Discussionmentioning
confidence: 99%